SS Yamani Enterprise / Nazaratulnisha Puaat - Puaat, Nazaratulnisha (2020)
Regarding to fulfil Fundamentals of Entrepreneurship (ENT300) course requirement, I need to conduct a case study. During the case study, I need to collect all information about an enterprise company to complete study case, so I decided to contact SS Yamani Enterprise Manager who is Encik Muhammad Faiz Bin Ramli to do an interview session. From the interview session, I have known about the company owner’s background and business profile, type of business model, products or services marketing. The company sells various apparels for the comfort of Haj pilgrims such as veils, telekung and accessories during pilgrimages